Non-Combustible Source Indoor Air Pollutants Concentration in Beauty Salons and Associated Self-Reported Health Problems Among the Beauty Salon Workers - Tagesse M; Deti M; Dadi D; Nigussie B; Eshetu TT; Tucho GT (Dove Medical Press, 2021)
Mihretu Tagesse,1 Mulunesh Deti,1 Dessalegn Dadi,1 Berhanu Nigussie,2 Tizita Teshome Eshetu,1 Gudina Terefe Tucho1 1Department of Environmental Health Science and Technology, Institute of Health, Jimma University, Jimma, Ethiopia; 2Department of Behavioral Sciences, College of Education and Behavioural Science, Jimma University, Jimma, EthiopiaCorrespondence: Gudina Terefe TuchoDepartment of Environmental Health Sciences and Technology, Jimma University, Jimma, EthiopiaTel +251 911703978Email guditerefe@gmail.comBackground: Cosmetic products emits Total Volatile Organic Compound (TVOC) and Particulate Matter with an aerodynamic diameter of 10 micrometers (PM10) of different sizes and characteristics with adverse health effects. Despite the increasing need for cosmetic products, related pollutants level of concentration from beauty salon is not well understood in developing countries.Objective: This study aims to assess indoor air pollutant concentrations in the beauty salon and self-reported health problems among the salon workers in Jimma town.Methods: A cross-sectional study design was used on 87 beauty salons from May 13– 24, 2019. The concentrations of PM10, TVOCs, CO2, room temperature, and relative humidity were measured and triangulated with the survey data collected through measurements and questionnaires. A statistical software package, SPSS v.21, was used to analyze the data. A binary logistic regression was used to analyze categorical data and linear regressions to predict pollutants level and associated health outcomes.Results: The results show that 93.1% of the respondents are females, and 85% were below 30 years old. More than 60% of the respondents were married individuals. 56.3% and 44.8% of the workers work over 10 hours per day and work the whole week. 34.6% of the workers reported as worked during pregnancy. About 70% of the workers know the harmful effects of cosmetics, benefits of ventilation, and Personal Protective Equipment (PPE) use, but only 19.4% use face masks. The majority (88.5%) reported health problems after starting work in the beauty salon. The mean volume of the beauty salon was 36.3 m3, with a mean PM10 concentration of 0.465 mg/m3 and a mean TVOC concentration of 1034.2 μg/m3. These air pollutants have shown a statistically significant association with self-reported health problems. Hence, urgent intervention with subsequent continuous awareness creation is needed to reduce the health consequences of a beauty salon’s indoor air pollutants.Keywords: indoor air pollutants, cosmetic products, PM10, TVOCs, beauty salon, Jimma town, Ethiopia